2022
DOI: 10.1093/jacamr/dlac009
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impacts of oral tetracycline class antibiotics on antimicrobial resistance in normal human flora

Abstract: Objectives There is interest in doxycycline as prophylaxis against sexually transmitted infections (STIs), but concern about antimicrobial resistance (AMR). We conducted a systematic review (CRD42021273301) of the impact of oral tetracycline-class antibiotics on AMR in normal flora. Methods We searched MEDLINE, EMBASE, the Cochrane Library (1940–2021) and conference proceedings (2014–21) for randomized controlled trials in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 52 publications
(57 reference statements)
0
13
0
1
Order By: Relevance
“…Tetracyclines are commonly used as one of the first-line antibiotics against a wide variety of non-life-threatening infections, including C. freundii infections [ 36 ]. The development of antibiotic resistance in C. freundii limits the treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Tetracyclines are commonly used as one of the first-line antibiotics against a wide variety of non-life-threatening infections, including C. freundii infections [ 36 ]. The development of antibiotic resistance in C. freundii limits the treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…This was highlighted in a recent systematic review, which found that oral tetracyclines for 2-18 weeks may increase AMR in subgingival, gastrointestinal and upper respiratory tract flora. 25 The USA Doxy-PEP study assessed AMR in nasal/oropharyngeal Staphylococcus aureus and pharyngeal non-gonococcal Neisseria species among 501 participants, and at month 12 found that participants on Doxy-PEP had lower carriage of S.aureus, compared with participants not on Doxy-PEP (29.2% vs 45.2%, P = 0.036), but a greater proportion of S. aureus culture samples were doxycycline resistant in the Doxy-PEP arm (11.7% vs 4.8%, P = 0.19). They found no increase in methicillin-resistant S. aureus (MRSA) overall, nor in doxycycline-resistant MRSA.…”
Section: Amr In Other (Non-target) Organismsmentioning
confidence: 99%
“…However, the antibiotic activity of DMC strongly decreases its potential for long-term treatments, such as those required for PD and other synucleinopathies. A systematic revision of oral tetracycline administration during 2–18 weeks showed an increase in antibiotic resistance in subgingival, gastrointestinal, and upper respiratory tract flora [ 14 ]. It is relevant to consider that the frequency of microbial antibiotic resistance continues to increase and has emerged as one of the most critical problems in medicine.…”
Section: Introductionmentioning
confidence: 99%